Workplace forums: a critical appraisal with specific reference to section 80 (2) and 84 of the Labour Relations Act, 66 of 1995 - Musi, Cagney John (Labour Enterprise Project, 2021)
The interim Constitution and the final Constitution, respectively Act 200 of 1996 and Act 108 of 1996, has ushered South Africa into a new era. An era that will be characterized by it's influence on our jurisprudential, political, socio-economic and religious rights. The Labour Relations Act 66 of 1995 in general and workplace forums in particular ushered our labour relations into a new era. It is our attempt by the legislature to foster corporatism at the enterprise. It is hoped that workplace participatory structures such as workplace forums will lead to: Better information flow and communication between management and the workers; better decision making by management; efficiency and productivity which will help the national economy. The legislative framework that regulates the establishment of workplace forums however, present certain problems. The major obstacles that the act create is, firstly; the granting of the sole right to call for the establishment of workplace forums to majority unions (section 80(2)) and secondly; the high threshold of 100 employees that is required by section 84 of the Labour Relations Act. These provisions are critically analysed from a comparative perspective. It is argued that the high threshold is totally inexplicable and unacceptable. It is contrary to the trend in Europe where experiments with workplace based structures were highly successful. This high threshold is also totally insensitive to the needs of SMME's. It is a known fact that workers in this sector are vulnerable, exploited and deserving of legislative or other forms of protection. The introduction or legislative facilitation of the establishment of workplace forums in SMME' s has potential to serve as a counterbalancing force. By engaging management and workers in a joint forum may of the problems in SMME's can be eradicated. The position of the majority unions is also untenable. The legislature has in fact disempowered those that it seeks to empower - the workers. In most countries studied, unions not necessarily majority unions have the right to trigger the process of establishing "workplace forums." In other countries, like Germany workers that are not union members can also trigger the process. This power that is give to majority unions also further marginalises SMME's. The SMME section is not sufficiently unionised because of the organizational problems that they present. In Britain for instance, only 8% of small companies are unionised. Unions will have logistic difficulties of organising and servicing a multitude of workplaces containing relatively small numbers of members. Section 80(2) and Section 84 of the Labour Relations Act will have to be revisited with a view of making workplace forums an all inclusive process and not one dominated by majority unions. The threshold for entitlement will have to be lowered so that more employees can enjoy the potential benefits of workplace base institutions.